Alterações fisiológicas e efeitos sedativos da associação entre buprenorfina e xilazina em equinos - Cruz, Fernando Silvério Ferreira da (2008)
The α₂-adrenergic receptor agonists are widely used in equine practice, especially in antalgic therapy, because they promote profound sedation and moderate visceral analgesia. The opioids are used in horses with some restriction due to the excitatory effects in this specie. The objective of this study was to evaluate the sedative effect, hemodynamic, pulmonary and digestory changes due to the neuroleptoanalgesic association of buprenorphine and different doses of xylazine. Six adults horses of both gender, weighting an average of 400 Kg. The animals were control of themselves, being divided into four groups, control group (CG) saline NaCl 0,9% solution administrated IV, and three other groups with buprenorphine 10 μg/kg associated to three different doses of xylazine, 0,25 mg/kg (BX25), 0,50 mg/kg (BX50) and 0,75 mg/kg (BX75) IV. Sedative effects, gastrointestinal motility, FC, f, SAP, MAP, DAP, blood gas tension analysis and core temperature were evaluated 30 min before, immediately before the administration of any treatment for basal values and after 5, 15 and every 15 min until 120 min post-treatment. Gastrointestinal motility was evaluated by the same period and for 12 hours, every 2 hours. Blood samples were collected at 0, 30 and 60 min. Parametric variables were analyzed with ANOVA, followed by Dunnett test for intra group and Tukey test between groups. For the non-parametric variable (intestinal motility) Wilcoxon test was used. Differences was considered significant when P<0.05. Intense sedative effect was observed in the three groups with the neuroleptoanalgesic association lasting 45 min in BX75 with profound ataxia. Intestinal motility decreased with 5 minutes after administration and remained decreased for 8 hours. Hemodynamic parameters started to increased after 30 min and no changes were observed in respiratory frequency and blood gas samples analysis, only HCO3- showed increase. Synergistic effect was observed, maintaining hemodynamic stability, with minimal pulmonary effects. The hypomotility observed must be considered when the association is used in horses with gastrointestinal disorders.